Kemajuan Teknologi Informasi Dan Telekomunikasi Terhadap Perkembangan Tindak Pidana Cyber Crime - Simanjuntak, Dahlan; Sudarto, Sudarto; Sujono, Sujono (Neolectura, 2025)
The advancement of information technology provides many conveniences for human life, but this advancement also simultaneously gives rise to various problems that are not easy to find a way out of. One of the problems that arises due to the development of information technology is the birth of crimes that are